Alveolar macrophage-derived type I interferons orchestrate innate immunity to RSV through recruitment of antiviral monocytes - Goritzka,M; Makris,S; Kausar,F; Durant,LR; Pereira,C; Kumagai,Y; Culley,FJ; Mack,M; Akira,S; Johansson,C (Journal of Experimental Medicine, 2015)
Type I interferons (IFNs) are important for host defense from viral infections, acting to restrict viral production in infected cells and to promote antiviral immune responses. However, the type I IFN system has also been associated with severe lung inflammatory disease in response to respiratory syncytial virus (RSV). Which cells produce type I IFNs upon RSV infection and how this directs immune responses to the virus, and potentially results in pathological inflammation, is unclear. Here, we show that alveolar macrophages (AMs) are the major source of type I IFNs upon RSV infection in mice. AMs detect RSV via mitochondrial antiviral signaling protein (MAVS)–coupled retinoic acid–inducible gene 1 (RIG-I)–like receptors (RLRs), and loss of MAVS greatly compromises innate immune restriction of RSV. This is largely attributable to loss of type I IFN–dependent induction of monocyte chemoattractants and subsequent reduced recruitment of inflammatory monocytes (infMo) to the lungs. Notably, the latter have potent antiviral activity and are essential to control infection and lessen disease severity. Thus, infMo recruitment constitutes an important and hitherto underappreciated, cell-extrinsic mechanism of type I IFN–mediated antiviral activity. Dysregulation of this system of host antiviral defense may underlie the development of RSV-induced severe lung inflammation.